Identification Model of Traditional Village Cultural Landscape Elements and Its Application from the Perspective of Living Heritage—A Case Study of Chentian Village in Wuhan - Rui Li; Yawei Zhang; Wanshi Li; Xuanxuan Xu (Buildings)
At present, there are limitations in the cognition of the elements of traditional village cultural landscapes, less excavation of the elements of production-type cultural landscapes, little attention to the layering of cultural landscapes in different periods and the correlation between the elements of different types of cultural landscapes, and insufficient research on the living continuity of traditional village cultural landscapes. In the context of rural cultural revitalization, it is necessary to explore strategies for the conservation and development of traditional village cultural landscapes from the perspective of living heritage. By interpreting the core connotation of the concepts of living heritage and cultural landscape, a model of traditional village cultural landscape elements and a framework for the identification of living elements are constructed. On the above basis, Chentian Village in Wuhan is taken as an example to identify its living cultural landscape elements, and to analyze the evolution of its cultural landscape elements from the dimension of “time-function”. In Chentian Village, a total of seventeen cultural landscapes were identified. Of these, ten were cultural landscapes with functional continuity and living heritage characteristics; three were cultural landscapes whose existing functions have changed significantly from their initial functions; and four were cultural landscapes that were inactive and have lost their original functions. Finally, this study proposes corresponding protection and development strategies for living heritage and non-living heritage of cultural landscapes.